The Mediating Role Of Personal And Social Responsibility In The Relationship Between Social Capital And Students' Altruism - Marziyeh Khalifeh Soltani; Reza Ghorban Jahromi; Morteza Nikoofar; Saeid Jafari (مطالعات روانشناسی تربیتی)
The aim of the present study was to investigate the mediating role of personal and social responsibility in the relationship between social capital and students' altruism. The research method was descriptive-survey type. And the statistical population was the students of physical education conservatories in Sistan and Baluchestan province, 285 person were selected as a statistical sample from the cluster sampling method. The data collection tools included was the standard questionnaires was by personal and social responsibility of Lee et al (2008), Social capital Khalifa Soltani et al. (2021) and altruism by Manzur and Olavarrieta (2021). Face and content validity were used to check the validity of the questionnaires.The data was analyzed through structural equation modeling using Lisrel software. Structural equation modeling analyzes confirmed the suitability of the proposed model. The results showed that the positive and direct effects of social capital and personal and social responsibility have positive and direct effects on altruism. Also, the positive and indirect effect of social capital through personal and social responsibility on students' altruism was shown. According to the results of the research, one of the methods of persuading students to engage in extra-role behaviors for altruism, improving social capital and personal and social responsibility.